How cyber security can protect your business : a guide for all stakeholders - Wright, Christopher (IT Governance Publishing, 2019)
Includes a checklist to help you focus on higher-priority cyber areas, this book explains how a strategic approach to cyber security can benefit your organization and provides an effective and efficient framework for managing cyber governance, risk and compliance. --